Home parenteral nutrition [ - Bozzetti, F. [ (Federico)]; Gossum, Andre van; Staun, Michael (CABI, 2006)
Chapters on the different aspects of home parenteral nutrition (HPN) in various countries as USA, Australia, New Zealand and European Union are presented, including discussions on the indications for HPN with regard to underlying disease (mainly intestial failure due to short bowel syndrome, radiation enteropathy, AIDS and cancer), nutritional requirements, HPN complications and epidemiological data (survival and mortality rates). Discussions on practical issues related to HPN, i.e. requirements, organization, funding, teaching, monitoring, etc. are also presented, as well as discussions on the contribution of pharmacists, dietitians, nurses and physicians. A specific section of the book is devoted to the use of HPN in paediatrics, i.e. infants or adolescents. The ethical and legal issues surrounding HPN are also presented in one chapter.